Shape matters: investigating the utility of geometric morphometric techniques in the deep-sea isopod family Macrostylidae (Isopoda: Asellota) - Casaubon, Anchita; Riehl, Torben (Frontiers in Marine Science, 2024)
Accurate taxonomic classification of deep-sea taxa is often impeded by the presence of highly morphologically similar but genetically distinct species. This issue is particularly pronounced in the isopods of the deep-sea family Macrostylidae, which exhibit remarkably low morphological variation despite significant genetic diversity. In this study, we present the first application of geometric morphometric techniques to 41 specimens across five species of deep-sea macrostylid isopods collected from Icelandic waters. Our results suggest that geometric morphometric techniques can effectively discriminate between macrostylid species. These techniques, hence, promise to be an important addition to the toolset of macrostylid taxonomists.